The Application of Communicative Strategies in Advertising Texts (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes the application of communicative strategies in advertising discourse and their effectiveness based on a linguopragmatic approach. In today’s global information environment, advertising media shape consumer culture by directly or indirectly influencing human consciousness. In this process, the advertising text functions not only as a transmitter of information but also as a powerful communicative tool that manages psychological and emotional states. Therefore, the correct selection of communicative strategies in advertising discourse and their integration with cultural, psychological, and linguistic factors is of utmost importance. The article highlights the linguistic features of advertising texts, the communicative strategies employed, and their mechanisms of influence on the audience, illustrated with examples. Additionally, the necessity of considering context, cultural codes, and psychological factors in the creation of advertising texts is emphasized. The article represents an attempt to integrate linguistic and pragmatic criteria in the analysis of advertising texts and may serve as a theoretical and practical foundation for scientific research conducted in this field.